2021
DOI: 10.31295/ijss.v4n1.1444
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of online Grammarly application in improving academic writing: review of experts experience

Abstract: This study aims to discuss the effectiveness of the Grammarly online application in improving academic writing through the experience of reviewing published papers. For that, we have reviewed a variety of literature and listened to the experiences of other academics published in various international journals. We chose descriptive qualitative content analysis. For example, it involves an in-depth analysis of each expert's experience with an exploratory phenomenological approach. To do this, we involve a coding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…There are quite a number of existing proofreader tools available as add-on or online tools for general writing problems on grammars, spellings and styles. Grammarly is quite popular for automatic proofreading in academic writing [38], [39], [40], [41]. Karyuatry and Rizqan [40] explains that Grammarly provides feedback on grammar errors and styling mistakes based on similarity patterns in real time.…”
Section: Discussion Of Some Existing Proofreading Toolsmentioning
confidence: 99%
“…There are quite a number of existing proofreader tools available as add-on or online tools for general writing problems on grammars, spellings and styles. Grammarly is quite popular for automatic proofreading in academic writing [38], [39], [40], [41]. Karyuatry and Rizqan [40] explains that Grammarly provides feedback on grammar errors and styling mistakes based on similarity patterns in real time.…”
Section: Discussion Of Some Existing Proofreading Toolsmentioning
confidence: 99%
“…LLMs have a wide spectrum of applications in writing, creating ambiguity about which applications warrant disclosure. Tools like Grammarly can be used to correct grammatical errors, improve readability, and provide text summaries ( Perdana et al 2021 , Dang et al 2022 ). Some LLM tools can translate text, aiding EFL researchers seeking to improve their publications in an English-dominated scientific community ( Guo et al 2022 , Chen 2023 , Ciaccio 2023 , Zhao 2023 ).…”
Section: Should the Disclosure Of Ai Llms In Scientific Writing Alway...mentioning
confidence: 99%
“…Thus, language instructors can also utilize Grammarly as an automated feedback tool on the student's work, which included essays, argumentative texts, and narrative texts (Thi & Nikolov, 2021). The benefits of Grammarly has been confirmed by many studies (see Perdana et al, 2021;Tambunan et al, 2022). These studies found that Grammarly can improve users' writing in terms of both grammar and language use.…”
Section: Introductionmentioning
confidence: 97%